Conservação frigorificada de pitaia orgânica irradiada - Fernandes, Luiza Maria de Souza [UNESP] (2011)
This work's objective was to evaluate the influence of different dosages of ionizing irradiation with 60Co in physical, physico-chemical, biochemical and chemical characteristics in post-harvest pitaya organic fruit of the Hylocereus undatus species, grown in the region of Itajobi - SP. The experiment was conducted in the Fruit and Vegetable Laboratory, Department of Agribusiness Management and Technology - FCA and Laboratory of Chemistry and Biochemistry, Department of Botany - IBB / UNESP - Botucatu - SP from March to April 2010. The radiation process was carried out at the Institute of Energy and Nuclear Research (IPEN) located in Sao Paulo. The fruits were harvested on the third day after the onset of color, selected, washed in running water and dried on paper towels. 20 fruits were, then, chosen, forming two replications of 10 fruits each, for characterization purposes without the interference of radiation and storage time. For treatments procedures, the fruits were packed in styrofoam trays, covered with PVC film, pre - cooled (8 ± oC for 24 hours) and subjected to different dosages of gamma irradiation (0.0, 0.2, 0.4; 0.6, 0.8 and 1.0 kGy of cobalt-60), and were subsequently stored in cold temperature of 8 ± 1 °C, with 90 ± 5% R U. The fruits were evaluated for their pH, soluble solids (SS), titratable acidity (TA), ratio (SS / TA), weight loss, respiratory activity, firmness, moisture, peel pulp relation, reducing sugars, non-reducing sugar, total sugars, phenolic compounds, flavonoid, protein, fiber, lipids and minerals on the day of the harvest for characterization and the results obtained were regarded as standard. After application of ionizing irradiation dosages, the fruits were evaluated after 0, 5, 10, 15 and 20 days of storage at a temperature of 8 ± 1 ºC for their pH, soluble solids (SS), titratable acidity (TA), ratio (SS / TA), weight loss, respiration rate, firmness ...